2021
DOI: 10.1155/2021/6940072
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and Prognosis: Drainage Skin-Bridge Sparing Surgery Combined with Fistulotomy versus Fistulotomy Only in the Treatment of Anal Fistula

Abstract: Objective. This study intends to analyze the difference in the efficacy of drainage skin-bridge sparing surgery combined fistulotomy (DSCF) and fistulotomy alone. Methods. 125 patients with anal fistula were enrolled as study subjects and randomly divided into control group (CG) and observation group (OG) by double-blind lottery. The CG received drainage skin-bridge sparing surgery with fistulotomy and the OG received fistulotomy only. Results. The VAS scores of the trauma in the OG were lower than those in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In a clinical study by Yang Wenzhi et al, the treatment group (180 cases) underwent anorectal sinus incision and drainage guided by three-dimensional transrectal ultrasound, while the control group received compound nystatin suppositories for local treatment. The results showed a cure rate of 94.44% and an efficacy rate of 100% in the treatment group, compared to a cure rate of 25% and an efficacy rate of 80% in the control group [7]. The results were similar to those of the study led by Xu Zheng et al…”
Section: Anorectal Sinus Incision and Drainage Seton Placement Surgerysupporting
confidence: 84%
“…In a clinical study by Yang Wenzhi et al, the treatment group (180 cases) underwent anorectal sinus incision and drainage guided by three-dimensional transrectal ultrasound, while the control group received compound nystatin suppositories for local treatment. The results showed a cure rate of 94.44% and an efficacy rate of 100% in the treatment group, compared to a cure rate of 25% and an efficacy rate of 80% in the control group [7]. The results were similar to those of the study led by Xu Zheng et al…”
Section: Anorectal Sinus Incision and Drainage Seton Placement Surgerysupporting
confidence: 84%
“…After initial screening of titles and abstracts, 329 articles were excluded, leaving 77. Following full-text reviews, 61 articles were further excluded, resulting in 16 studies, 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] all in Chinese, with a total sample size of 1124 patients, including 567 in the observation group and 557 in the control group. The characteristics of the included studies and patients are shown in Table 1.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Effectiveness and Prognosis: Drainage Skin-Bridge Sparing Surgery Combined with Fistulotomy vs. Fistulotomy Only in the Treatment of Anal Fistula” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%